2018
DOI: 10.3390/nu10030325
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Dietary Supplements Exert Anti-Inflammatory Action and Limit Ganglion Cell Degeneration in the Retina of the EAE Mouse Model of Multiple Sclerosis

Abstract: Optic neuritis is an acute inflammatory demyelinating disorder of the optic nerve (ON) and is an initial symptom of multiple sclerosis (MS). Optic neuritis is characterized by ON degeneration and retinal ganglion cell (RGC) loss that contributes to permanent visual disability and lacks a reliable treatment. Here, we used the experimental autoimmune encephalomyelitis (EAE) mouse model of MS, a well-established model also for optic neuritis. In this model, C57BL6 mice, intraperitoneally injected with a fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
(75 reference statements)
2
15
0
1
Order By: Relevance
“…As shown by our previous and present results, diet supplementation with FAs efficiently counteracts the effects of MOG when its administration starts the day of immunization. This protocol is in line with previous studies in which diet supplements are given after the pathology has been induced by MOG [ 5 ] although, the possibility exists that the incorporation of FAs into the diet before MOG-induction may be viewed as a preventive measure. Indeed, recent epidemiologic studies have reported a decreased incidence of MS among individuals with high intake of PUFAs [ 38 , 39 , 40 ] although conflicting results on a possible relationship between PUFA intake and decreased MS risk are also reported [ 41 ].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…As shown by our previous and present results, diet supplementation with FAs efficiently counteracts the effects of MOG when its administration starts the day of immunization. This protocol is in line with previous studies in which diet supplements are given after the pathology has been induced by MOG [ 5 ] although, the possibility exists that the incorporation of FAs into the diet before MOG-induction may be viewed as a preventive measure. Indeed, recent epidemiologic studies have reported a decreased incidence of MS among individuals with high intake of PUFAs [ 38 , 39 , 40 ] although conflicting results on a possible relationship between PUFA intake and decreased MS risk are also reported [ 41 ].…”
Section: Discussionsupporting
confidence: 78%
“…In line with a previous study [ 5 ], 9 MOG-treated mice and nine controls received by oral gavage (starting from the day of immunization until the day 16 when the animals were sacrificed) a mixture of saturated and unsaturated FAs including 20% of saturated FAs, while 17.5% of unsaturated FAs. Of this mixture, 3.75 mg suspended in 200 μL of 10% sucrose in water were administered to the animals.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…The death of RGCs has been considered the main cause of vision loss after an episode of ON (10,11). In the animal model of relapsing/remitting EAE, RGC apoptosis begins within a few days after onset of optic nerve in ammation (12,13), suggesting that axonal damage and cell loss are induced by optic nerve in ammation.…”
Section: Introductionmentioning
confidence: 99%